Pożytki z zastosowania budżetowania kosztów i przychodów w zakładach opieki zdrowotnej - Hass-Symotiuk, Maria (Benefits of Application Cost and Revenue Budgeting in Health Care Institutions, 2005)
Against a background of essence and objectives of budgeting in health care institutions in the article there are presented conditions that must be fulfilled to utilise this tool to control them and possible benefits to obtain. These benefits mean improvements in the "quality" of management (as a result of, inter alia, or-dering coordination of activities aimed at realisation of objectives that are specified in the budgets, retionalising organisation of health care services, increase in staff motivation), and in consequence, better utilisation of factors of production and improvements in economic performance of the institution.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 201-207